2022
DOI: 10.3389/fmars.2022.856643
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Diazotroph Distributions in the Western South Atlantic

Abstract: Inputs of new nitrogen by cyanobacterial diazotrophs are critical to ocean ecosystem structure and function. Relative to other ocean regions, there is a lack of data on the distribution of these microbes in the western South Atlantic. Here, the abundance of six diazotroph phylotypes: Trichodesmium, Crocosphaera, UCYN-A, Richelia associated with Rhizosolenia (Het-1) or Hemiaulus (Het-2), and Calothrix associated with Chaetoceros (Het-3) was measured by quantitative PCR (qPCR) of the nifH gene along a transect e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…These results confirmed our hypothesis that the intrusion of Kuroshio greatly enhanced N 2 fixation in the ECSYS. Based on the present finding in the Kuroshio and recent evidence in the Gulf Stream (Palter et al., 2020), Brazil Current (Detoni et al., 2016, 2022) and East Australian Current (Armbrecht et al., 2015), we infer that the intrusion of western boundary currents into marginal seas fuels regional N 2 fixation. Our study provided high spatial resolution data sets of NFR in the ECSYS during summer, which would be useful for understanding N and C biogeochemical process, although the present use of original bubble method might underestimate the NFR.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These results confirmed our hypothesis that the intrusion of Kuroshio greatly enhanced N 2 fixation in the ECSYS. Based on the present finding in the Kuroshio and recent evidence in the Gulf Stream (Palter et al., 2020), Brazil Current (Detoni et al., 2016, 2022) and East Australian Current (Armbrecht et al., 2015), we infer that the intrusion of western boundary currents into marginal seas fuels regional N 2 fixation. Our study provided high spatial resolution data sets of NFR in the ECSYS during summer, which would be useful for understanding N and C biogeochemical process, although the present use of original bubble method might underestimate the NFR.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, their intrusions into marginal seas may fuel regional N 2 fixation. Emerging evidence has shown abundant diazotrophs or active N 2 fixation in subtropical-temperate seas affected by the Gulf Stream (Palter et al, 2020) and Brazil Current (Detoni et al, 2016(Detoni et al, , 2022. However, responses of diazotrophic composition and N 2 fixation to the intrusions of western boundary currents including Kuroshio remain poorly understood.…”
mentioning
confidence: 99%
“…While the presence of DDA hosts, both infected and uninfected, in oligotrophic OSW waters is not surprising, their presence in the Mekong River (MRW) and coastal (OnSW) waters suggests that the host diatoms at least are able to grow under a broad range of physical and nutrient conditions, confirming the findings of Grosse et al (2010) and Bombar et al (2011). Interestingly, Detoni et al (2022) recently reported very low DDA abundances from a survey of the South Atlantic using quantitative PCR to quantify nifH phylotypes. The factors that control diazotroph community composition may differ among ocean basins and/ or hemispheres, possibilities that can only be evaluated through much broader scale surveys of diazotroph abundances.…”
Section: Dda Distribution In the South China Seamentioning
confidence: 69%
“…Distributions of unicellular diazotrophs, especially in the subtropics, have been conventionally assayed by a combination of phycoerythrin detection from nano‐sized cyanobacteria by epifluorescence microscopic observation, flow cytometry, or by fluorometric analysis in the Pacific Ocean (Bonnet et al., 2009; Dore et al., 2002; Dugenne et al., 2020; Falcon et al., 2004; Kitajima et al., 2009; Needoba et al., 2007; Neveux et al., 1999; Stenegren et al., 2018; Wilson et al., 2017), Atlantic Ocean (Foster et al., 2007; Krupke et al., 2013), and Mediterranean Sea (Bonnet et al., 2011). Detection of UCYN‐B nif H amplicons has been reported from the Pacific Ocean (Berthelot et al., 2017; Bonnet et al., 2008; Church, Jenkins, et al., 2005; Church, Short, et al., 2005; Fong et al., 2008; Grabowski et al., 2008; Gradoville et al., 2020; Halm et al., 2012; Moisander et al., 2010; Needoba et al., 2007; Shiozaki et al., 2015, 2017; Shiozaki, Kondo, et al., 2018; Stenegren et al., 2018; Watkins‐Brandt et al., 2011; Zehr et al., 2001), Atlantic Ocean (Detoni et al., 2022; Foster et al., 2007; Foster, Subramaniam, & Zehr, 2009; Goebel et al., 2010; Krupke et al., 2013; Langlois et al., 2008; Martinez‐Perez et al., 2016; Mulholland et al., 2012; Turk‐Kubo et al., 2011), South China Sea (Kong et al., 2011; Moisander et al., 2008; Shiozaki, Ijichi, et al., 2014; Wen et al., 2017), Indian Ocean (Shiozaki, Ijichi, et al., 2014), Arabian Sea (Mazard et al., 2004), Red Sea (Foster, Paytan, & Zehr, 2009), and Mekong River plume (Bombar et al., 2011). Luo et al.…”
Section: Distributionmentioning
confidence: 99%